Preschool behavior problems: antecedent factors of family structure, family change, and parenting behaviors - Rizzo, Marc C., author; Lunkenheimer, Erika S., advisor; MacPhee, David L., committee member; Rosén, Lee A., committee member (Colorado State University. Libraries, 2013)
Research indicates that there are meaningful relationships between family-based variables, parent-based variables, and child behavioral problems, specifically externalizing and internalizing patterns. This research indicates that family structure, family change, and certain parenting practices are all important in relation to child behavior problems. This study aims to help clarify how these various environmental constituents may contribute to child behavior problems by studying the role that family structure, family change, and maladaptive parenting have with one another. Participants in this study include 100 families in the local community with children ages 3 to 4 years old, and data were collected at two time points. Using 2x2 ANOVAs and bivariate correlations, there are significant main and interaction effects in child externalizing and internalizing behavior problems by family type, and a negative correlation between mother laxness and partner laxness with child behavior problems. Linear regressions with bootstrapping show that traditional families with both high and low change and lax maternal parenting are predictive of child behavior problems. A discussion regarding the role of internal and external factors such as, community, timing, sample-related issues, and differences in behavioral and parenting raters is included, along with limitations of the current study and future directions.
Keywords: child behavior; overreactive parenting; lax parenting; family structure; family change